1994
DOI: 10.1136/gut.35.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole v ranitidine for prevention of relapse in reflux oesophagitis. A controlled double blind trial of their efficacy and safety.

Abstract: The aim of this study was to compare recurrence rates of reflux oesophagitis (after endoscopic healing with omeprazole) over a 12 month period of randomised, double blind, maintenance treatment with either daily omeprazole (20 mg every morning; n=53), weekend omeprazole (20 mg on three consecutive days a week, n=55) or daily ranitidine (150 mg twice daily, n=51). Patients were assessed for relapse by endoscopy (with gastric biopsy) at six and 12 months, or in the event of symptomatic recurrence, and serum gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0
4

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(87 citation statements)
references
References 13 publications
8
75
0
4
Order By: Relevance
“…In addition, an endoscopic examination was performed after 12 months in all patients still remaining in the studies of Dent et al 28 and Hallerba Èck et al 29 …”
Section: Endoscopic Grading Of Oesophagitismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an endoscopic examination was performed after 12 months in all patients still remaining in the studies of Dent et al 28 and Hallerba Èck et al 29 …”
Section: Endoscopic Grading Of Oesophagitismentioning
confidence: 99%
“…In individual patients oesophagitis usually relapsed to the same grade or to a lower grade compared to the Table 3. Patient demographics by study Zeitoun et al 25 Staerk Laursen et al 26 Sontag et al 27 Dent et al 28 Hallerba Èck et al 29 initial pre-treatment severity grade. In the omeprazole 20 mg daily group no patient had a more severe endoscopic lesion at relapse, while deterioration of the oesophagitis at relapse was found in one patient in the 10 mg group, ®ve patients in the ranitidine group, nine patients in the omeprazole weekend therapy group, and 11 patients in the placebo group.…”
Section: Remission Ratesmentioning
confidence: 99%
“…Thus, comparative studies have demonstrated that protonpump inhibitors provided far superior GERD healing compared with histamine H 2 -receptor antagonists (H 2 -RAs). [1][2][3][4][5][6][7][8][9][10][11] In Japan, omeprazole 10 mg, as well as 20 mg, is widely used as maintenance therapy for GERD. Hallerback et al reported that maintenance therapy with omeprazole 10 mg was superior to ranitidine 300 mg 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced doses of PPIs have not been shown consistently to be effective long-term in the therapy of GERD. This includes alternate-day omeprazole (84) or so-called weekend therapy (85). A daily dose of 10 mg may be superior to standarddose ranitidine (86).…”
Section: Because Gerd Is a Chronic Condition Continuous Therapy To Cmentioning
confidence: 99%